Mercado de trabalho e controle do processo de trabalho na indústria: um estudo no Norte de Minas - Roney Versiani Sindeaux (2012)
The present study attempts to broaden the understanding of control of work process in the industry and its relation to the changes that have occurred in workers profile in the labor market, specifically in the North of Minas Gerais. This area of Minas Gerais, had its industrialization induced by the State Government and, over the past 50 years, was created a labor market accustomed to the dynamics of the industry but also the coronelista posture of practices of management historically consolidated. However, the time that consolidated this practice has been also changing them. Thus, wage relationship once consolidated, has been modified with changes in companies in the market and economic context in which they operate and the characteristics of the labor market. It is this dynamic of change that this thesis analyzes. What changes have occurred? What impacts these changes have resulted in the form of wage relations? The search for answers to these and other issues arising is constructed from a theoretical analysis on control of work process, and his Marxist perspective and its aspect of the Theory of Regulation. Later, from the analysis of the northern region of Minas Gerais, specifically history of its development and context of industrial activity, labor market and control of work process in the regional industry. The result obtained and highlighted on this conclusion points to the evidence of initial perspective that motivated the study. Whichever changes in context and in the labor market have been changing the form of wage relations, specifically in the structure and organization of the work process. However, some results meet the positioning until now consolidated by researcher, presenting new perspectives for understanding the wage relation and process of work control in the North of Minas Gerais.